HUBUNGAN ANTARA PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DAN MOTIVASI BELAJAR PADA KUALITAS PEMBELAJARAN DI MADRASAH ALIYAH NEGERI 2 KOTA JAMBI - Meilinda, Melvi; Hakim, Lukman; Putra, Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the relationship between the use of interactive learning media and learning motivation on learning quality at Madrasah Aliyah Negeri 2 Jambi City. The background of this research is based on the phenomenon of low student participation, limited interaction in the classroom, and varying levels of learning motivation, which affect the overall quality of learning. This study aims to analyze the relationship between interactive learning media and learning motivation, both partially and simultaneously, on learning quality. The research employed a quantitative approach with a correlational design. The population consisted of 399 students, and a sample of 117 students was selected using purposive sampling techniques. Data were collected through questionnaires and documentation, and analyzed using descriptive and inferential statistics with the help of SPSS. The results showed that the use of interactive learning media and students’ learning motivation were both in the moderate category. Furthermore, the findings revealed a significant relationship between interactive learning media and learning quality, as well as between learning motivation and learning quality. Simultaneously, both variables showed a significant relationship with learning quality. These findings indicate that the integration of interactive media and strong learning motivation plays an important role in improving the quality of learning.